The benefits of hepatitis C virus cure: Every rose has thorns. Issue 4 (19th February 2018) - Salmon, D.; Mondelli, M. U.; Maticic, M.; Arends, J. E.; ,
Summary: To examine mid‐term benefits on hepatic complications, extrahepatic clinical syndromes and quality of life associated with HCV cure; to review the few safety issues linked to oral direct‐acting antivirals (DAAs); and to discuss the potential population benefits of reducing the burden of HCV infection. DAAs cure HCV infection in more than 95% of patients. The halting of liver inflammation and fibrosis progression translates into both hepatic and extrahepatic benefits and reduces the need for liver transplantation. A reduction in the frequency of extrahepatic manifestations such as mixed cryoglobulinaemia and vasculitis and improvements in quality of life and fatigue have also been described. A few safety issues linked to DAAs such as the potential recurrence of aggressive HCC, the flares of hepatitis B virus in patients with overt or occult HBV infection are been discussed. Curing HCV infection also has a high potential to reduce the burden of HCV infection at the population level. With widespread scaling up of HCV treatment, several modeling studies suggest that major reductions in HCV prevalence and incidence are possible, and that elimination of viral hepatitis is an achievable target by 2030.